Clinical applications of circulating tumor cells in hepatocellular carcinoma - Hua, Yinggang; Dong, Jingqing; Hong, Jinsong; Wang, Bailin; Yan, Yong; Li, Zhiming (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is a highly malignant tumor and ranked as the fourth cause of cancer-related mortality. The poor clinical prognosis is due to an advanced stage and resistance to systemic treatment. There are no obvious clinical symptoms in the early stage and the existing diagnostic methods have some limitations, but the early diagnosis rate remains low. Novel effective biomarkers are urgently needed for early diagnosis and tumor surveillance to improve the survival of HCC patients. Circulating tumor cells (CTCs) in peripheral blood is a very small amount of cancer cells shed from primary or metastatic tumor sites into the blood system, and are closely related to the metastasis of various solid tumors. CTCs escape from blood vessels and settle in target organs, then form micro-metastasis. Epithelial-mesenchymal transformation (EMT) plays a crucial role in distant metastasis, which confers strong invasiveness to CTCs. The fact that CTCs can provide complete cellular biological information, which allows CTCs to be one of the most promising liquid biopsy targets. Recent studies have shown that CTCs are good candidates for early diagnosis, prognosis evaluation of metastasis or recurrence, and even a potential therapeutic target in patients with HCC. It may be a new indicator for clinical application in the future. In this review, we introduce the enrichment methods and EMT phenotype of CTCs and focus on clinical application in patients with HCC.